Trait coordination, mechanical behaviour and growth form plasticity of Amborella trichopoda under variation in canopy openness. (18th August 2015) - Trueba, Santiago; Isnard, Sandrine; Barthélémy, Daniel; Olson, Mark E.
Abstract : Finding that Amborella trichopoda is sister to the rest of the angiosperms has raised the question of whether it shares certain key functional trait characteristics and plastic responses apparently widespread within the angiosperms at large. With this in mind, Trueba et al. tested the hypothesis that local canopy openness induces plastic responses in Amborella. The authors provide evidence of intraspecific coordination between leaf and stem economic spectra in this key species. Moreover, by presenting the first architectural and biomechanical characterization of Amborella, their study offers new insights for the understanding of the early sequences of angiosperm form evolution. Abstract: Understanding the distribution of traits across the angiosperm phylogeny helps map the nested hierarchy of features that characterize key nodes. Finding that Amborella is sister to the rest of the angiosperms has raised the question of whether it shares certain key functional trait characteristics, and plastic responses apparently widespread within the angiosperms at large. With this in mind, we test the hypothesis that local canopy openness induces plastic responses. We used this variation in morphological and functional traits to estimate the pervasiveness of trait scaling and leaf and stem economics. We studied the architecture of Amborella and how it varies under different degrees of canopy openness. We analyzed the coordination of 12 leaf and stem structural and functional traits, and the association of this covariation with differing morphologies. The Amborella habit is made up of a series of sympodial modules that vary in size and branching pattern under different canopy openness. Amborella stems vary from self-supporting to semi-scandent. Changes in stem elongation and leaf size in Amborella produce distinct morphologies under different light environments. Correlations were found between most leaf and stem functional traits. Stem tissue rigidity decreased with increasing canopy openness. Despite substantial modulation of leaf size and leaf mass per area by light availability, branches in different light environments had similar leaf area-stem size scaling. The sympodial growth observed in Amborella could point to an angiosperm synapomorphy. Our study provides evidence of intraspecific coordination between leaf and stem economic spectra. Trait variation along these spectra is likely adaptive under different light environments and is consistent with these plastic responses having been present in the angiosperm common ancestor.